Enzymatic hydrolysis of botryosphaeran and laminarin by beta-1,3-glucanases produced by Botryosphaeria rhodina and Trichoderma harzianum Rifai - Giese, E. C.; Covizzi, L. G.; Dekker, RFH; Monteiro, N. K.; da Silva, MDC; Barbosa, A. M. (Elsevier B.V., 2006)
Botryosphaeran, a (1 -> 3; 1 -> 6)-beta-D-glucan produced by Botryosphaeria rhodina, and laminarin were hydrolysed by two fungal beta-glucanases predominantly of the 1,3-type produced by B. rhodina and Trichoderma harzianum Rifai grown on botryosphaeran as sole carbon source. Both beta-glucanase preparations presented different modes of attack on botryosphaeran and laminarin. Laminarin was hydrolysed to the extent of similar to 50% in 1 hand 100% within 24 h, and its hydrolysis products were mainly glucose and gentiobiose, and lesser amounts of laminaribiose and oligosaccharides of DP 3-4 during the early stages of hydrolysis, while botryosphaeran 'yielded mainly glucose and gentiobiose with some trisaccharide, but no laminaribiose or tetrasaccharide when hydrolysed by the T. harzianum enzyme. By contrast, B. rhodina beta-1,3-glucanases produced predominantly glucose during all stages of botryosphaeran hydrolysis. Some physicochemical properties of the 1,3- and 1,6-beta-glucanases, and beta-glucosidases contained in the two fungal P-glucanase preparations are also described for the first time. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: Botryosphaeria rhodina; botryosphaeran; enzymatic hydrolysis beta-1,3-glucanases; laminarin; Trichoderma harzianum Rifai